Antimicrobial resistance pattern of clinical isolate of Pseudomonas aeruginosa in the University of Malaya Medical Center, Malaysia - Al-Kabsi, A.M.; Yusof, M.Y.M.; Sekaran, S.D. (2011)
Pseudomonas aeruginosa is considered as one of the leading causes of nosocomial infections. The start of antimicrobial therapy is often empirical and selective pressure on panel of antibiotics; therefore, it is important to know the susceptibility pattern of pathogens in order to select the most appropriate antibiotic. The aim of the current study is to update the rational empirical antimicrobial therapy recommendations. Antimicrobial resistance was done using the E-test method. Urine and wound swab samples were the highest encountered isolates; results were interpreted according to National Committee for Clinical Laboratory Standards guidelines. A total of 88 clinical isolates of P. aeruginosa were collected randomly from April 2009 to March 2010 from the University of Malaya Medical Center. P. aeruginosa isolated from various clinical samples has lost susceptibility and showed increasing resistance to Gentamicin with 94.3%, followed by (ciprofloxacin) 92%, (ceftazidime) 89.8%, (imipenem) 73.9%, Pipracilline/tazobactam 61.4%, (aztreonam) 52.3%, and (amikacin) 50% and only susceptible to colistin with 92%. In conclusion, most of the isolates showed high levels of resistance to examined antibiotics except colistin and this may indicate the importance of antibiotic susceptibility testing and optimal treatment by combination of drugs.